Life between memory and hope : the survivors of the Holocaust in occupied Germany - Mankowitz, Zeev W. (Studies in the social and cultural history of modern warfare, 2002)
This is the remarkable story of the 250,000 Holocaust survivors who converged on the American Zone of Occupied Germany from 1945 to 1948. They envisaged themselves as the living bridge between destruction and rebirth, the last remnants of a world destroyed and the active agents of its return to life. Much of what has been written elsewhere looks at the Surviving Remnant through the eyes of others and thus has often failed to disclose the tragic complexity of their lives together with their remarkable political and social achievements. Despite having lost everyone and everything, they got on with their lives, they married, had children and worked for a better future. They did not surrender to the deformities of suffering and managed to preserve their humanity intact. Mankowitz uses largely inaccessible archival material to give a moving and sensitive account of this neglected area in the aftermath of the Holocaust.